Uji Aktivitas Jahe (Zingiber officinale) terhadap Metabolisme dan Pencernaan - Khalim Purnomo; Ardi Mustakim (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the activity of ginger (Zingiber officinale) on metabolism and digestion through a laboratory experimental approach. Metabolism and the digestive system play a crucial role in maintaining physiological balance, and disturbances in these systems can affect nutrient utilization and overall health. Ginger has long been used as a traditional herbal remedy and is known to contain bioactive compounds such as gingerol, shogaol, and zingerone, which are believed to support digestive and metabolic functions. The research was conducted using ginger extract prepared through an extraction process under controlled laboratory conditions. Observations focused on changes in metabolic responses and digestive activity following the administration of ginger extract. The study employed a descriptive experimental design to provide an objective overview of ginger’s biological activity. The results indicated a gradual improvement in digestive activity and metabolic responses after treatment with ginger extract. These changes suggest that ginger extract has the potential to enhance digestive efficiency and support metabolic processes. The findings provide scientific support for the traditional use of ginger as a natural ingredient in maintaining metabolic and digestive health and may serve as a preliminary reference for further research using quantitative and clinical approaches.